Chusquea contrerasii and C. guzmanii (Poaceae, Bambusoideae, Bambuseae, Chusqueinae), two new endemic species from Jalisco, Mexico - Ruiz-Sanchez, Eduardo; Romero-Guzman, Rafael; Flores-Argüelles, Alejandra; Ortiz-Brunel, Juan Pablo; Clark, Lynn G. (Phytotaxa, 2021)
Chusquea is the richest genus of woody bamboo worldwide, with 191 described species distributed from Mexico, the Antilles, and Central America to southern South America. Mexico has 22 described species distributed along the Trans-Mexican Volcanic Belt, Sierra Madre del Sur, Sierra Madre Oriental and Chiapas Highlands. Two of the five subgenera recognized within Chusquea, subg. Chusquea and subg. Swallenochloa, are present in Mexico. Chusquea subg. Chusquea is classified into six sections, of which Chusquea sect. Longifoliae has 12 described species; four of them are present in Mexico. Based on recent morphological work that included an extensive taxonomic investigation of herbarium specimens and fieldwork carried out in the Mexican state of Jalisco, two new Chusquea species, C. contrerasii and C. guzmanii, are described and illustrated here. Both species are endemic to Jalisco, Mexico. Morphologically, Chusquea contrerasii and C. guzmanni are similar to C. nelsonii. A comparative morphological table is presented, and in addition to the scientific illustrations, photographs of both species are also presented here. These two new species increase the total number of Chusquea species in Mexico to 24. Sect. Longifoliae now has 14 species, six of them distributed in Mexico and the total diversity of Chusquea increases to 193 described species.